Building an infrastructure to support the development, conduct, and reporting of informative clinical studies: The Rockefeller University experience. Issue 1 (13th April 2023) - Kost, Rhonda G.; Devine, Rita K.; Fernands, Mark; Gottesman, Riva; Kandpal, Manoj; MacArthur, Robert B.; O'Sullivan, Barbara; Romanick, Michelle; Ronning, Andrea; Schlesinger, Sarah; Tobin, Jonathan N.; Vaughan, Roger; et al.
Abstract: Introduction: Clinical trials are a vital component of translational science, providing crucial information on the efficacy and safety of new interventions and forming the basis for regulatory approval and/or clinical adoption. At the same time, they are complex to design, conduct, monitor, and report successfully. Concerns over the last two decades about the quality of the design and the lack of completion and reporting of clinical trials, characterized as a lack of "informativeness, " highlighted by the experience during the COVID-19 pandemic, have led to several initiatives to address the serious shortcomings of the United States clinical research enterprise. Methods and Results: Against this background, we detail the policies, procedures, and programs that we have developed in The Rockefeller University Center for Clinical and Translational Science (CCTS), supported by a Clinical and Translational Science Award (CTSA) program grant since 2006, to support the development, conduct, and reporting of informative clinical studies. Conclusions: We have focused on building a data-driven infrastructure to both assist individual investigators and bring translational science to each element of the clinical investigation process, with the goal of both generating new knowledge and accelerating the uptake of that knowledge into practice.